2017
DOI: 10.1186/s12883-017-0988-x
|View full text |Cite
|
Sign up to set email alerts
|

Normothermia after decompressive surgery for space-occupying middle cerebral artery infarction: a protocol-based approach

Abstract: BackgroundModerate hypothermia after decompressive surgery might not be beneficial for stroke patients. However, normothermia may prove to be an effective method of enhancing neurological outcomes. The study aims were to evaluate the application of a pre-specified normothermia protocol in stroke patients after decompressive surgery and its impact on temperature load, and to describe the functional outcome of patients at 12 months after treatment.MethodsWe analysed patients with space-occupying middle cerebral … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 28 publications
0
4
0
Order By: Relevance
“…Another study reported that hypothermia within 6 h of onset was associated with severe neurological dysfunction in the early stages of cerebral infarction 37 . Other studies have also demonstrated that hypothermia therapy may not be beneficial for patients with malignant middle cerebral artery occlusion cerebral infarction, in part because of the higher incidence of adverse events in patients treated with hypothermia 38 , 39 . Importantly, DCI after the rupture of an intracranial aneurysm is a significant cause of mortality 40 .…”
Section: Discussionmentioning
confidence: 99%
“…Another study reported that hypothermia within 6 h of onset was associated with severe neurological dysfunction in the early stages of cerebral infarction 37 . Other studies have also demonstrated that hypothermia therapy may not be beneficial for patients with malignant middle cerebral artery occlusion cerebral infarction, in part because of the higher incidence of adverse events in patients treated with hypothermia 38 , 39 . Importantly, DCI after the rupture of an intracranial aneurysm is a significant cause of mortality 40 .…”
Section: Discussionmentioning
confidence: 99%
“…However, the detailed mechanism by which hypothermia exerts its protective effects on brain tissues remains unclear. Conversely, recent studies showed that moderate hypothermia might not be beneficial for stroke patients (19), as it did not reduce the likelihood of death or disability in patients with neonatal encephalopathy, but rather, it significantly increased the risk of death (20). Rahmig et al (19) found that, in surgically treated patients with middle carotid artery (MCA) infarction, the risk of death was lower for individuals with high body temperature than for those with low body temperature.…”
Section: Discussionmentioning
confidence: 99%
“…Conversely, recent studies showed that moderate hypothermia might not be beneficial for stroke patients (19), as it did not reduce the likelihood of death or disability in patients with neonatal encephalopathy, but rather, it significantly increased the risk of death (20). Rahmig et al (19) found that, in surgically treated patients with middle carotid artery (MCA) infarction, the risk of death was lower for individuals with high body temperature than for those with low body temperature. The discrepancies observed in the abovementioned findings may be explained by the fact that low body temperature and therapeutic hypothermia may be different conditions.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, focusing on a single BT record may increase the bias risk. Temperature load (TL) [ 5 ] may be a method to this limitation, defined as the sum of BT above/below the targeted temperature level multiplied by the duration (hours). For instance, the TL of hyperthermia (> 38.3 °C) within 72 h should be calculated as follows—step 1: ; step 2: .…”
mentioning
confidence: 99%